Analysis Of Fast Ship Requirements In The Lembar Crossing Port - Padangbai In 2018 - Surnata Surnata; Bambang Setiawan (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2020)
Transportation needs in an area caused by the interaction between social and political activities, as well as tourism in the area. Transportation plays a very important role in the success of the development of an area, which has a role as a liaison between one region and another separated by the presence of water, the role of transportation is also very closely related to development, and stimulates new activities in the development of the transportation system into a very important and very useful role in the smooth development of the wheel, strengthening unity and unity that affects all aspects of life. The conditions of West Lombok Regency which is close to Bali Island which is separated by the Lombok Strait, this causes crossing transportation is the main transportation of goods or passengers that can be reached by the community in supporting equitable development. Crossing transportation has an important role to provide support for economic growth, especially crossing. The position of transportation becomes one of the decisive elements in order to guarantee the economic development of the community. As the economy progresses, the role of transportation increases. This is due to the economic dependence on transportation to be greater because it must always be guaranteed smoothness in the flow of goods and passengers quickly, cheaply and safely from Padangbai Port to Lembar Harbor or vice versa. Lembar Crossing Port is one of the Crossing Ports located in West Lombok Regency which serves the Lembar - Padangbai Crossing. At the Crossing Port Lembar there is a ferry transportation company operated by PT. Indonesia Ferry ASDP Branch of Lembar.